Efficacy and safety of adjunctive perampanel 4 mg/d for the treatment of focal seizures: A pooled post hoc analysis of four randomized, double‐blind, phase III studies - Steinhoff, Bernhard J. (Epilepsia, 2020)
OBJECTIVE: This post hoc analysis evaluated the efficacy and safety of adjunctive perampanel 4 mg/d received as modal dose, which may have differed from randomized dose, for treatment of focal seizures. METHODS: Data were pooled from four randomized, double‐blind, placebo‐controlled, phase III studies of adjunctive perampanel in patients (aged ≥12 years) with focal seizures, with/without focal to bilateral tonic‐clonic (FBTC) seizures: studies 304 (NCT00699972), 305 (NCT00699582), 306 (NCT00700310), and 335 (NCT01618695). Efficacy assessments included median percentage reductions in seizure frequency per 28 days and seizure‐freedom rates for patients receiving placebo and perampanel 4 mg/d (modal dose). Treatment‐emergent adverse events (TEAEs) were assessed in patients receiving perampanel 4 mg/d at their TEAE onset. Outcomes were also assessed with/without enzyme‐inducing antiseizure medications (EIASMs). RESULTS: The full analysis set included 979 patients with focal seizures (placebo: n = 616 [235 with FBTC seizures]; perampanel 4 mg/d: n = 363 [134 with FBTC seizures]). Compared with placebo, perampanel 4 mg/d conferred significantly greater median percentage reductions in seizure frequency per 28 days for focal (12.6% vs 21.1%; P = .0004) and FBTC seizures (17.4% vs 49.8%; P < .0001), and seizure‐freedom rates for focal (0.8% vs 3.6%; P = .0018) and FBTC seizures (11.1% vs 18.7%; P = .0424). Seizure improvements with perampanel 4 mg/d were greater without EIASMs than with EIASMs. For assessment of TEAEs, overall 1376 patients with focal seizures received perampanel 4 mg/d at any time (FBTC seizures, n = 499). TEAEs with perampanel 4 mg/d occurred in 419 of 1376 (30.5%) and 148 of 499 (29.7%) patients with focal and FBTC seizures, respectively; most common was dizziness. The proportion of TEAEs was similar with or without EIASMs. SIGNIFICANCE: This post hoc analysis showed adjunctive perampanel 4 mg/d was efficacious and well tolerated in patients with focal seizures, with or without FBTC seizures. This dose may be a valuable treatment option in patients unable to tolerate higher perampanel doses up to 12 mg/d.